Obtaining a second opinion is a neglected source of health care inequalities - Jochanan Benbassat (BMC, 2019)
Abstract Observational studies have detected discrepancies between two expert interpreters of imaging and histopathological studies. Furthermore, in a substantial proportion of patients, an independent second opinion disagreed with the first one. Therefore, it is widely accepted that patients have a right to obtain a second opinion and, in case of divergent opinions, to deliberate and choose the option that they believe is most consistent with their individual circumstances. However, doctors are less likely to inform old and poorly educated patients about the possibility of seeking a second opinion, and this may contribute to healthcare inequalities. Hence the importance of (a) promoting doctors' self-awareness of a possible tendency to discriminate against old and poorly educated patients, and (b) creating programs within the healthcare system that would help patients in seeking a second opinion, suggest specialists for the specific problem of the patient, and provide tools to reconcile between discrepant opinions.